(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article provides information about the development and ways of establishing intelligence in children. From the moment a child is born, guiding him or her toward development, indicating the work that needs to be done to develop his or her own intelligence.